A Discrete-Time Decoupled Current Control Scheme Applied to VSC-Based Three-Phase Three-Line Systems. (21st August 2011) - Wang, Hui; Li, Qingmin; Wang, Guangzhu; Tan, Xingguo
Abstract : Accurate current control of the voltage source converters (VSCs) is one of the key research subjects in modern power electronics. To achieve a preferable solution to current coupling effect in the VSC-based three-phase three-line system, a discrete-time decoupled current control strategy is proposed in the paper. With integration of the α - β transform and two independent current controllers, the proposed methodology can effectively implement decoupled control of the three-phase currents, which can thereby eliminate the impact from the neutral-point voltage especially under asymmetrical loading conditions. Control performance under digital realization was characterized with extensive tests on a shunt active power filter (SAPF) platform. Both the simulative and experimental results have demonstrated that the SAPF could function well and thereby verified the feasibility and effectiveness of the proposed current control methodology.